Любовь внарезку: повесть / В. А. Алексеева, В. С. Алексеев - Алексеева Валентина Алексеевна (Лучшие книги для девочек, 2009)
Экземпляры: ф.20 (20150715) / Инвентарный номер: 51832 / Цена: 30. 00. / Сис.шифр: Р2 / Авт.знак: А 47 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44